Medieval Welsh Pilgrimage, c.1100–1500 - Hurlock, Kathryn. author. aut Link
XV, 262 p. 4 illus.
Keywords: Medieval Welsh Pilgrimage, c.1100–1500 examines one of the most popular expressions of religious belief in medieval Europe—from the promotion of particular sites for political, religious, and financial reasons to the experience of pilgrims and their impact on the Welsh landscape. Addressing a major gap in Welsh Studies, Kathryn Hurlock peels back the historical and religious layers of these holy pilgrimage sites to explore what motivated pilgrims to visit these particular sites, how family and locality drove the development of certain destinations, what pilgrims expected from their experience, how they engaged with pilgrimage in person or virtually, and what they saw, smelled, heard, and did when they reached their ultimate goal.